2017
DOI: 10.1111/ijsw.12269
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonstandard work schedules on workers' health: A mediating role of work‐to‐family conflict

Abstract: This study examined the relationship between nonstandard work schedules, work‐to‐family conflict, and health status in the USA adult population. Based on pooled data from the 2006, 2010, and 2014 General Social Survey (N = 4,108), this study found that nonstandard work schedules were associated with poor self‐rated health and increased days of poor physical and mental health. Also, results from the causal mediation analysis indicated that the relationship between nonstandard work schedules and health status wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Corroborating the results of previous studies (e.g., McLoyd et al, 2008; Cho, 2018), we found that parents working full-time and 40 h or more per week and with a shiftwork schedule reported higher levels of work-family conflict. Parents working full-time and more than 40 h per week have objectively less time for their family, which can lead them to experience greater difficulty in successfully managing family and work roles.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Corroborating the results of previous studies (e.g., McLoyd et al, 2008; Cho, 2018), we found that parents working full-time and 40 h or more per week and with a shiftwork schedule reported higher levels of work-family conflict. Parents working full-time and more than 40 h per week have objectively less time for their family, which can lead them to experience greater difficulty in successfully managing family and work roles.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, parents with a shift work schedule usually work on weekends, work evening and night shifts, and have irregular or rotating shifts. This type of work schedule, often called “unsociable work” (Strazdins et al, 2006), may be highly disruptive for family routines (McLoyd et al, 2008) and may lead parents to experience a greater instability and a lower perception of control over their lives and to have less time and energy resources for performing their family role, which may result in a greater perception that work demands are negatively interfering with their family demands (Cho, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-standard work schedules interfere with circadian rhythms and are negatively associated with sleep quality (Costa 2003; Maume et al 2009; Vogel et al 2012; Wight, Raley, and Bianchi 2008). Non-standard work schedules are also associated with stress (Bara and Arber 2009), anxiety and irritability (Costa 2003), and reports of worse self-rated health and mental health (Cho 2017; Costa 2003; Fenwick and Tausig 2001, 2004; Knutsson 2003; Presser 2003; Rajaratnam and Arendt 2001).…”
Section: Precarious Schedulesmentioning
confidence: 99%
“…Work generates income and influences health, social interactions, family relationships, and so forth (Lipscomb, Loomis, McDonald, Argue, & Wing, ). The work environment is the most important factor for human well‐being (Cho, ; Daniels, Watson, & Gedikli, ; Danna & Griffin, ; Gerstel & Clawson, ; Kirschenbaum, Oigenblick, & Goldberg, ; Sparks, Faragher, & Cooper, ) and the achievement of inclusive economic growth (Marmot, ). Along with this, other factors, including social interaction and technology, influence the dynamics of the economy and have an irreversible effect on socioeconomic factors, health, and the overall well‐being of humankind.…”
Section: Nswss and Economicsmentioning
confidence: 99%